Sufi Authority in “Post-Modern” Muslim Societies - Katkova, Irina R. (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2020)
While the beginning of the 21st century demonstrated the emergence of various distinctive styles of Sufism, the existing studies of Sufi practice and discourse in various countries across the world illustrate how social modern forms and techniques are now among the conditions of possibility for a great many movements that are concerned to extend the Islamic tradition, traditions of practice and piety. Yet, modern scholarship represents relatively little known area of Sufi leadership tradition as well as the role of shaykh as a mediating agent in Muslim societies. Fulfilling this scientific gap, this paper is aimed at examining the ways in which we could better understand the role of Sufi shaykh and the production of their authorities in post-modern Muslim societies. In doing so, the paper gives ample emphasis on theoretical discussion about tradition in mystical Islam, and about the ways in which such tradition gives influence to the mediating role played by a Sufi shaykh in society, with a particular case study of the Naqshbandiyah tradition in West Sumatra, Indonesia. This paper reveals the important dimension of traditions of how Sufi shaykhs practice the ideal of Prophet as spiritual masters, within the regional form of Islam, or as mediating shaykhs today, that enable Muslims to pursue a spiritual path within the conflicting situations and pressure of modern life.